Analisis Strategi dan Penguatan Diplomasi dalam Penanganan Sengketa Perbatasan Negara (Pusat Riset dan Inovasi Nasional, 2026)
The establishment of national territorial boundaries is a strategic priority to safeguard sovereignty, maintain security stability, and strengthen bilateral relations between Indonesia and Malaysia as well as Timor-Leste. As of 2024, there remain nine Outstanding Boundary Problems (OBP) with Malaysia and two unresolved segments with Timor-Leste. These issues stem from the continued relevance of outdated colonial agreements, limited diplomatic capacity, weak inter-agency coordination, and minimal support from modern surveying technology. Based on an analysis of four policy alternatives using the criteria of effectiveness, efficiency, and long-term impact, the Strengthening of Intensive Bilateral Diplomacy has been identified as the priority policy. Implementation is directed to the Badan Nasional Pengelola Perbatasan (BNPP) as the main coordinator, supported by regulatory frameworks, diplomatic resources, and cross-ministerial/institutional coordination. Through this strategy, the resolution of pending boundary segments can be accelerated, legal certainty over national territory can be strengthened, security stability in border areas can be improved, and bilateral relations can become closer. Furthermore, Indonesia needs to strengthen diplomatic strategies, leverage technology, and enhance inter-agency coordination to accelerate the resolution of national border disputes. This policy directly contributes to achieving territorial sovereignty and sustainable development toward Indonesia Vision 2045.